PENGARUH TEKNIK OBTURASI SALURAN AKAR DENGAN KONDENSASI LATERAL, WARM GUTTA-PERCHA DAN CARRIER-BASED GUTTA-PERCHA TERHADAP KEBOCORAN APIKAL - , Christine Windayani Inan, drg. Diatri Nari Ratih, M.Kes., SpKG, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this study was to investigate the effect of root canal obturation techniques using lateral condensation, warm gutta-percha, and carrier-based guttapercha respectively on apical leakage. Thirty intact mandibular premolar teeth were used in this study. All teeth were instrumented with crown-down technique using hand-use Protaper. All teeth were assigned randomly into 3 groups of 10 each teeth. The first group was obturated using lateral condensation, the second group using warm gutta-percha (System B), and the third group using carrier-based gutta-percha (Thermafil). Each group was placed into container filled with moist cotton, and stored in 370C incubator for fourteen days. All subjects were coated with two layers of nail polish, subsequently by one layer of sticky wax except 2 mm from the apical foramina. Subjects were then put into 12 ml centrifuge tubes containing 2% methylene blue and centrifuged at 800 rpm for 3 minutes. Furthermore, all subjects were sectioned longitudinally. The penetration of methylene blue as the apical leakage indicator was observed using stereo-microscope with 60 magnifications. Data were obtained from the longest penetration from the apex to coronal and calibrated within micrometers (μm) unit. The result of this study showed that apical leakage occurred in all the obturation techniques. The lateral condensation group revealed the greatest apical leakage (8976 ± 550.78 μm), followed by System B group (6336 ± 430.07 μm), and Thermafil group was the lowest (3420 ± 460.43 μm). One-way ANAVA analysis demonstrated that root canal obturation technique using lateral condensation, System B, and Thermafil affected on the apical leakage (p<0.05). LSD analysis showed a significant difference occurred among all of the treatment groups (p<0.05). The conclusion of this study was root canal obturation techniques influenced on the apical leakage. The lowest apical leakage occurred in carrier-based guttapercha technique group (Thermafil).